Determining the environmentally responsible behaviour of tourists while visiting selected resorts in Limpopo - Maboya, M. K. (Vaal University of Technology, 2019)
Tourism is a fast-developing industry globally, and the impacts of tourism are exceedingly diverse. The relationship between the environment and tourism has assumed a unique position in research through the development of tourism studies over the years. From an economic viewpoint, tourism is aimed at bringing income to local communities. It also could also increase and spread economic development, thus reducing the inequalities in income distribution by providing and creating employment opportunities. However, from an ecological standpoint, tourism poses a threat to the delicate environment. Thus, the pressure on natural resources remains a major problem globally, and the fact that tourism-related activities and facilities such as resorts contribute to the scarcity and overuse of resources is of great concern. The rapid growth in tourist numbers poses a significant threat to natural resources, more so tourists are significant consumers of natural resources such as water and electricity while on holiday. Overuse and depletion of these natural resources can cause environmental degradation in and around a destination. Even though some tourists hold positive environmental attitudes, they may not behave environmentally responsible while visiting resorts, because they want to experience the destination in full. Behavioural change is a complex process involving the interaction between numerous variables of which attitude is only one attribute. Attitude itself is also a complex attribute which is challenging to define and may involve multiple and even contradictory values. Previous studies indicate that positive attitudes toward the environment do not necessarily lead to environmentally responsible behaviour. Researchers have found a weak relationship between attitudes and behaviour. Although there is not a direct or linear relationship between attitude and behaviour, they may have significant causal effects on behaviour. Suffice to say, however, viiattitudes, especially strong specific and narrowly defined attitudes that have been acquired through direct experience, that influence the person’s self-interest and are accessible, have a strong effect on behaviour. For this reason, a general indication of the variable ‘environmental attitudes’ was obtained by recoding the respondents’ identification and ratings of severe environmental problems when visiting LWR in Limpopo. The measurement of environmental concern or rather behaviour is generally regarded as an integrated component of broader attitudinal dispositions. This study attempted to determine whether tourists are behaving in an environmentally responsible manner while visiting selected resorts in Limpopo South Africa. This was approached based on an empirical study which followed a quantitative research design. A non-probability, convenience sampling method by means of a web-survey was adopted. The target population for this study were tourists to all LWR (Limpopo Wildlife Resorts) in Limpopo South Africa. Once the data was collected, it was captured and processed by means of SPSS (Statistical Package for Social Sciences). Environmentally responsible behaviour of tourists visiting LWR was analysed by means of descriptive statistics, using factor analysis and ANOVA. With the information gathered, the researcher wanted to test if there was a difference in visitor behaviour in comparison to their attitudes toward the environment. ANOVA was used to compare the difference in visitor’s behaviour and attitudes while visiting resorts and the use of factor analysis as a procedure was necessary for data reduction and summarisation. Therefore, a one-way analysis of variance (ANOVA) was applied to investigate how tourist environmentally responsible behaviour differs between visitor profiles. The data showed that females agreed more strongly with statements empathetic to the environment than male respondents did. Furthermore, the data showed that as one becomes older, so the agreement with the opinion of empathetic opinion to the environment becomes larger. The apathetic environmental opinion factor shows an opposite tendency, namely as one grows older, the agreement with the apathetic opinion factor becomes less. Awareness has become heightened, which is shown in the visitor’s value of nature and leads to environmentally conscious behaviour and activities to preserve the environment. Moreover, an increased concern of the environment has made consumers more aware of the environmental impacts of their viiipurchase decision concerning the service industry. The increased awareness of environmental impacts of tourism has led to the emergence of tourist called, among others, environmentally responsible tourist. Therefore, one can say that tourist as consumers are becoming more aware of the importance of protecting the environment and more involved in practising environmentally friendly behaviour while on holiday.
M. Tech. (Department of Tourism and Hospitality Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Environment; Responsible tourism; Sustainable tourism; Resorts; Dissertations, Academic -- South Africa; Tourism -- Limpopo; Sustainable tourism; Resorts -- South Africa